For a given input value n, the function g outputs a value m to satisfy the following equation.
3m-5n=11
Write a formula for g(n), in terms of n.
g(n)=
Answer:
3m-5n=11
the function g outputs a value m. It means we need to solve for m in terms of n
solve the given equation for m
3m-5n=11
Inverse of -5n is +5n so we add 5n on both sides
3m-5n + 5n=11 + 5n
3m = 11 + 5n
Divide by 3 on both sides
m =
![(11+5n)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/c4a8zmbqs5ywd39vnzzv13c96f8ugm4psl.png)
The function g outputs the value m
So g(n) =
![(11+5n)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/c4a8zmbqs5ywd39vnzzv13c96f8ugm4psl.png)